Paranoia - Luketic, Robert, 1973-; Hemsworth, Liam, 1990-; Oldman, Gary; Heard, Amber, 1986-; Junkie XL, 1967-; Finder, Joseph (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2013)
An entry-level employee at a powerful tech corporation is enlisted by the company's CEO to spy on a rival corporation.
Originally released as a motion picture in 2013.
Based on the novel by Joseph Finder.
Dolby digital 5.1, wide screen 2.40:1.
Features: theatrical trailer.
Camera, David Tattersall ; production designers, David Brisbin, Missy Stewart ; editors, Dany Cooper, Tracy Adams ; music, Junkie XL.
Liam Hemsworth, Gary Oldman, Amber Heard, Harrison Ford, Lucas Till, Embeth Davidtz.
Keywords: Finder, Joseph -- Film adaptations; Espionage -- Drama; Corporations -- Corrupt practices -- Drama; Fiction films; Thriller films; Based on the book; Feature films